PENGARUH VARIASI KONSENTRASI HPMC TERHADAP SIFAT FISIK GEL EKSTRAK KULIT PISANG AGUNG SEMERU (Musa paradisiaca L.) - Eryani, Mikhania Christiningtyas; Siddiq, Hadi Barru Hakam Fajar; Rashati, Dewi; Safitri, Risma Khoiro (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
The aims of this study was to determine the effect of HPMC variation concentration to the physical properties of Semeru Agung banana (Musa paradisiaca L.) skin extract gel. Gel was formulated with various HPMC concentration namely F1 (2%), F2 (3%) and F3 (4%). Gel was evaluated organoleptic, homogeinity, pH, viscosity, spreadbility and adhesion value. The results showed that F2 meet the organoleptic requirements while F1 and F3 did not meet. All formulas are homogeneous. The results of the pH test showed that the pH value of F1 was 5.9 ± 0; F2 of 5.8± 0 ; F3 of 5.9 ± 0. The results of the viscosity test showed that the viscosity value of F1 was 150 ± 0 dPas; F2 of 250 ± 0 dPas; F3 of 300 ± 0 dPas. The results of the dispersion test showed that the dispersion value of F1 was 5.6 ± 0.06 cm; F2 of 5.3 ± 0.29 cm ; F3 is 4.0 ± 0.12 cm. The results of the adhesion test showed that the value of the F1 adhesiveness was 11.04 ± 0.43 seconds; F2 of 17.4 ± 1.47 seconds; F3 is 24.2 ± 2.44 seconds. It is known that variations in HPMC concentration affect gel texture, viscosity, spreadability and adhesion, and have no effect on gel smell, color and pH.